Misclassification rate of the angiographically identified culprit lesion in NSTEMI. (3rd October 2022) - Ekstroem, K; Loenborg, J; Nepper-Cristensen, L; Holmvang, L; Joshi, F R; Iversen, A Z; Madsen, P L; Olsen, N T; Pedersen, F; Soerensen, R; Tilsted, H H; Vejlstrup, N G; et al.
Abstract: Background: Correct identification of the culprit lesion in NSTEMI is essential, in particular for patients in whom a culprit-only strategy is attractive (e.g., elderly and frail patients). However, when identifying the culprit lesion in NSTEMI, angiography can be ambiguous and correct culprit identification can therefore be challenging when based on angiography, ECG- and echocardiographic changes alone (standard-of-care). In fact, this challenge remains unresolved and is a continuous limitation in guidelines and in the few clinical trials investigating the revascularization strategy in NSTEMI. Purpose: We aimed to investigate the agreement between angiography and cardiac magnetic resonance (CMR) and optical coherence tomography (OCT) in identifying the culprit lesion in non-ST segment elevation myocardial infarction (NSTEMI). Methods: In two centres we prospectively enrolled 104 patients. CMR was performed prior to angiography. Operators, blinded to CMR, identified a culprit lesion based on angiography and standard-of-care. OCT was subsequently performed on operator-suspected culprit lesions and stenoses ≥50% diameter. CMR and OCT were reviewed blinded to angiographic culprit identification. Myocardial oedema on CMR was considered the reference standard for a culprit. In the absence of oedema, OCT was used. In case of multiple suspected OCT-lesions, hierarchical criteria for culprit identification were used: acute thrombus > plaque rupture with a cavity > organising thrombus > dissection > calcific nodule. Results: The majority of included patients were male (75%) at a mean 63 years of age. Obstructive disease was observed in 85 (82%) patients, of which 53 (51%) had multivessel disease. On a patient-level, angiography identified a culprit lesion in 90 (87%) patients, of which CMR/OCT only identified a culprit in 74 (82%) patients. This constituted a moderate overall positive predictive value of angiography, which was found inferior to CMR/OCT in identifying the culprit lesion. On a lesion-level, CMR/OCT identified a different culprit lesion than angiography in 12 (16%) patients. Of these, only one patient did not receive revascularization of the true culprit lesion. Moreover, in the 14 patients without an angiographic culprit, CMR/OCT identified a culprit in 7 (50%) patients. Thus, angiography including standard-of-care falsely identified the culprit lesion in overall 35 (34%) patients: 7 false negatives, 16 false positive at patient-level, and 12 misclassified angiographic culprits on lesion-level (Figure 1). Specifically, OCT identified 13% misclassified culprit lesions in proximal segments, and provided an added diagnostic value. Conclusions: Angiography misclassified the culprit lesion in one in three patients with NSTEMI with respect to both presence and location. OCT complemented angiography in ambiguous cases which underscores the value of OCT in aiding treatment and diagnosis in NSTEMI. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Research Grant at Rigshospitalet, Copenhagen University Hospital, DenmarkNovo Nordisk Foundation, Denmark